Rivaroxaban for the treatment of venous thromboembolism - Kucher, Nils; Aujesky, Drahomir; Beer, Jürg H.; Mazzolai, Lucia; Baldi, Thomas; Banyai, Martin; Hayoz, Daniel; Kaeslin, Thomas; Korte, Wolfgang; Escher, Robert; Husmann, Marc; Frauchiger, Beat; Baumgartner, Iris; Spirk, David (Thrombosis and Haemostasis, 2016)
We investigated three-month clinical outcomes in patients with venous thromboembolism (VTE) treated with rivaroxaban or conventional anticoagulation in routine clinical practice. Between November 2012 and February 2015, 2,062 consecutive patients with VTE from 11 acute care hospitals in Switzerland were enrolled in the SWIss Venous ThromboEmbolism Registry (SWIVTER). Overall, 417 (20 %) patients were treated with rivaroxaban. In comparison to 1,645 patients on conventional anticoagulation, patients on rivaroxaban were younger (56 ± 18 vs. 65 ± 17 years; p<0.001), less often had pulmonary embolism (38 % vs 66 %; p<0.001), hypertension (26 % vs 41 %; p<0.001), cancer (10 % vs 28 %; p<0.001), congestive heart failure (10 % vs 17 %; p=0.001), diabetes (8 % vs 15 %; p<0.001), chronic lung disease (7 % vs 13 %; p=0.001), renal insufficiency (7 % vs 13 %; p=0.001), recent surgery (7 % vs 14 %; p<0.001), and acute coronary syndrome (1 % vs 4 %; p=0.009). VTE reperfusion therapy was more frequently used (28 % vs 9 %; p<0.001) and indefinite-duration anticoagulation treatment less often planned (26 % vs 39 %; p<0.001), respectively. In the propensity score-adjusted population, the risk of recurrent VTE was similar in patients on rivaroxaban vs conventional anticoagulation (1.2 % vs 2.1 %, hazard ratio [HR] 0.55, 95 % confidence interval [CI] 0.18–1.65; p=0.29); the risk of major bleeding was also similar, respectively (0.5 % vs 0.5 %, HR 1.00, 95 %CI 0.14–7.07; p=1.00). Conventional anticoagulation is still frequently used for the treatment of VTE, particularly in the elderly and those with comorbidities. Early clinical outcomes were comparable between propensity score-adjusted patient populations on rivaroxaban and conventional anticoagulation.
Keywords: Anticoagulation; rivaroxaban; venous thromboembolism